Current strategies for intratumoural immunotherapy – Beyond immune checkpoint inhibition. (November 2021) - Yuan, Jianda; Khilnani, Anuradha; Brody, Joshua; Andtbacka, Robert H.I.; Hu-Lieskovan, Siwen; Luke, Jason J.; Diab, Adi; Marabelle, Aurelien; Snyder, Alexandra; Cao, Z. Alexander; Hodi, F. Stephen
Abstract: Immunotherapy has revolutionised cancer treatment through restoration of host antitumour immune response. Immune checkpoint inhibitors (ICIs) confer durable responses in only a subset of patients. Mechanisms of ICI resistance to improve durable response rates and overall survival are an area of intense clinical research. Robust clinical development is ongoing to evaluate novel combination therapies to overcome ICI resistance, including targeting immunoregulatory pathways in the tumour microenvironment. Intratumoural (IT) immunotherapies such as toll-like receptor agonists, stimulator of interferon-induced gene agonists, retinoic-inducible gene I–like receptor agonists and oncolytic viruses may represent potential combination treatment options to overcome ICI resistance. Use of IT immunotherapies in combination with ICIs may alter the tumour microenvironment to address resistance mechanisms and improve antitumour response. Optimisation of IT immunotherapy clinical trials will elucidate resistance mechanisms, facilitate clinical trial design, define pharmacodynamic predictors that identify patients who may most benefit and inform clinical development of combination immunotherapy regimens. Here we provide an overview of IT immunotherapy principles, mechanisms of action, categories of IT immunotherapeutics, emerging data, clinical development strategies, response assessment, dose and schedule determination, clinical trial design and translational study design. Highlights: Resistance to immune checkpoint inhibitor (ICI) therapy represents a large unmet medical need. Intratumoural (IT) immunotherapies are potential options to overcome ICI resistance. IT immunotherapies may inform ICI regimens to identify resistance mechanisms. Analysing blood and injected and non-injected tumours informs clinical development. Future therapies may overcome resistance by immune priming through activated antigen-presenting cells.